Studies The Dynamic Of The Teaching Strategies In English ‎And Mathematic Classrooms - Abdullah Al Maqbali (WISE Pendidikan Indonesia, 2025)
Teaching strategies play a critical role in shaping classroom interaction and student engagement across subject areas; however, their implementation often varies according to disciplinary contexts. This study aims to explore and compare the dynamics of teaching strategies employed in English and mathematics classrooms within the General Foundation Programme at a public university in Oman. Adopting a qualitative ethnographic design, data were collected through non participant classroom observations conducted in one English class and one mathematics class, supported by structured observation checklists and detailed field notes. The findings reveal a clear divergence in instructional approaches, with the English classroom predominantly employing learner centered strategies that foster active participation, collaboration, and instructional responsiveness, while the mathematics classroom relied largely on teacher centered instruction emphasizing content delivery and procedural accuracy. These contrasting approaches significantly influenced classroom climate, patterns of interaction, and levels of student engagement. The study contributes to the literature by providing classroom based, observational evidence of subject-specific instructional dynamics within a shared institutional context. The findings imply that professional development programs should emphasize adaptive pedagogical strategies that enable teachers, particularly in traditionally teacher centered subjects such as mathematics, to integrate learner centered elements in ways that enhance student engagement without compromising instructional efficiency.